UPAYA PENINGKATAN OMZET PENJUALAN MELALUI PEMASARAN DIGITAL PADA UMKM TELUR ASIN DAN PUYUH MADE DI DESA GONDANG KECAMATAN TAMAN KABUPATEN PEMALANG - Tri Handayani; Arum Yuli Harsih; Muhammad Taufik; Laela May Az Zahra; Mokhammad Umar Abdul Aziz Al Farizi (Migunani Nusantara: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service activity, namely the Business Work Lecture, started from June 17 - July 17, 2023 at one of the MSMEs, namely Salted Eggs and MADE Quail owned by Mrs. Maesaroh, which is located in Gondang Village, Taman District, Pemalang Regency. In this activity we make all efforts to facilitate and assist MSMEs in order to improve business progress by using various programs in the form of: 1.) Creation of UMKM Location Points on Google Maps, 2.) Creation of social media accounts on Instagram, Facebook, and Tokopedia, 3.) Creation of UMKM Logo, 4.) Banner Creation, 5.) Creation of NIB (Business Identification Number), 6.) Making UMKM Product Packaging, Labels, Stickers, 7.) etc. The benefits obtained after this activity ended were obtaining Social Media and Marketplace Promotion accounts, getting a Business Identification Number (NIB), there are signs indicating the location of MSMEs, addresses that can be detected on Google Maps.